INTEGRATION OF GPS AND GIS IN ESTABLISHING LAND INFORMATION SYSTEM OF CTU-BARILI PARCELS OF LANDS - Mondejar, Jeremy P (Journal of Agriculture and Technology Management, 2015)
Establishing land information system is a valuable resource in managing vast area of lands. In this study, GIS and GPS are integrated as a modern method of generating relatively spatially accurate and operationally effective cadastral and other related information database. CTU-Barili Campus lots are about 100 hectare. Since its transfer from its former location (Lahug, Cebu City) to its recent location (Cagay, Barili, Cebu), the administration and the faculty of agricultural engineering have no sufficient knowledge on its land boundaries or property lines. This paper focuses on establishing its land information system in terms of property lines, land-use and topography to a projected real world coordinate system (PRWCS). Due to the availability of geospatial data and tools, it is now easier to establish, link and combine land information in a bigger spatial setting. As a result, useable relatively accurate GIS and GPS based digital land information of CTU-Barili Campus can serve as a decision support system for the school’s property management and sustainable development.